A Retrospective Study Investigating Injury Incidence and Factors Associated with Injury among Belly Dancers. Issue 1 (March 2019) - Milner, Siobhan C.; Gray, Andrew; Bussey, Melanie
Belly dance is an appreciably under researched dance form. As such, little is known of the injury prevalence and risk factors for injury among this dance population. Therefore, the primary objective of this study was to examine the most common injury sites and to identify potential factors associated with injury risk within the belly dance community of New Zealand over a 12-month retrospective period. Dancers who had practiced or performed belly dance during that time span were surveyed using an online or paper-based questionnaire. One hundred and nine injury questionnaires (all from female dancers) qualified for the final analysis. The participants had a median age of 44.3 years and danced a median of 3.0 hours per week. The injury rate was 37% (40 injuries in 109 dancers surveyed), the injury incidence proportion was 24.8% (27 dancers reporting at least one injury), and the per hour injury incidence rate was 1.69 per 1, 000 dance hours. Of the two most recently sustained injuries reported, lower limb injuries were the most common, followed by trunk injuries. Age, total dance hours per week, and participation in a non-dance exercise regimen of any kind were associated with a decreased risk of injury; performing regularly was associated with an increased injury rate. It is concluded that an understanding of the incidence and sites of injuries may help create awareness that belly dance can be injurious, and subsequently lead to the development of future interventions.